Reduced Life Expectancy Model for Effects of Long Term Exposure on Lethal Toxicity with Fish. (26th December 2013) - Verma, Vibha; Yu, Qiming J.; Connell, Des W.
Abstract : A model based on the concept of reduction in life expectancy (RLE model) as a result of long term exposure to toxicant has been developed which has normal life expectancy (NLT) as a fixed limiting point for a species. The model is based on the equation (LC50 = a  ln(LT50 ) + b ) where a and b are constants. It was evaluated by plotting ln LT50 against LC50 with data on organic toxicants obtained from the scientific literature. Linear relationships between LC50 and ln LT50 were obtained and a Calculated NLT was derived from the plots. The Calculated NLT obtained was in good agreement with the Reported NLT obtained from the literature. Estimation of toxicity at any exposure time and concentration is possible using the model. The use of NLT as a reference point is important since it provides a data point independent of the toxicity data set and limits the data to the range where toxicity occurs. This novel approach, which represents a departure from Haber's rule, can be used to estimate long term toxicity from limited available acute toxicity data for fish exposed to organic biocides.